Arduino-Based Real Time Air Quality and Pollution Monitoring System (International Journal of Innovative Research in Computer Science & Technology, 2018)
Now-a-days air pollution is one of the most  important concern of the world. Air pollution may  evolve from anthropogenic or natural sources. Air  pollutants of atmospheric substances like CO, CO2,  SO2, NO2, and O3 suspended particulate matter (SPM),  repairable suspended particulate matter (RSPM), and  volatile organic compounds (VOCs) have a great effect  on the people health. Most of the major cities in  developing countries and most cities of the developed  countries are suffering from it. Thus to develop a real  time air quality and pollution monitoring system is  critical. We have developed an arduino based air  pollution detector which combined a small-sized,  minimum-cost sensor to an arduino microcontroller  unit. The advantages of the detector, have a reliable  stability, rapid response recovery and long-life  features. It is affordable, user-friendly, low-cost and  minimum-power requirement hardware which is  appropriate for mobile measurement, as well as  comprehensible data collection. It has a processing  software able to analyze, collected quality data with  high precision. Simple instrument which can be  commercially utilized.
Keywords: Air pollution; ardunio; gas sensor; anthropogenic; atmosphere